2018
DOI: 10.1126/science.aar7711
|View full text |Cite
|
Sign up to set email alerts
|

The first horse herders and the impact of early Bronze Age steppe expansions into Asia

Abstract: The Yamnaya expansions from the western steppe into Europe and Asia during the Early Bronze Age (~3000 BCE) are believed to have brought with them Indo-European languages and possibly horse husbandry. We analyzed 74 ancient whole-genome sequences from across Inner Asia and Anatolia and show that the Botai people associated with the earliest horse husbandry derived from a hunter-gatherer population deeply diverged from the Yamnaya. Our results also suggest distinct migrations bringing West Eurasian ancestry int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
278
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 292 publications
(306 citation statements)
references
References 116 publications
10
278
4
2
Order By: Relevance
“…Recent paleogenomic studies have revealed a dynamic population history on the Eurasian Steppe, with continental-scale migration events on the Western Steppe coinciding with Bronze Age transformations of Europe, the Near East, and the Caucasus (Allentoft et al, 2015; de Barros Damgaard et al, 2018; Damgaard et al, 2018; Haak et al, 2015; Mathieson et al, 2015; Wang et al, 2019). However, despite advances in understanding the genetic prehistory of the Western Steppe, the prehistoric population dynamics on the Eastern Steppe remain poorly understood (de Barros Damgaard et al, 2018; Jeong et al, 2018). The Eastern Steppe is a great expanse of grasslands, forest-steppe, and desert-steppe extending more than 2,500 km from the Altai-Sayan mountain range in the west to northeastern China in the east (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent paleogenomic studies have revealed a dynamic population history on the Eurasian Steppe, with continental-scale migration events on the Western Steppe coinciding with Bronze Age transformations of Europe, the Near East, and the Caucasus (Allentoft et al, 2015; de Barros Damgaard et al, 2018; Damgaard et al, 2018; Haak et al, 2015; Mathieson et al, 2015; Wang et al, 2019). However, despite advances in understanding the genetic prehistory of the Western Steppe, the prehistoric population dynamics on the Eastern Steppe remain poorly understood (de Barros Damgaard et al, 2018; Jeong et al, 2018). The Eastern Steppe is a great expanse of grasslands, forest-steppe, and desert-steppe extending more than 2,500 km from the Altai-Sayan mountain range in the west to northeastern China in the east (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The Eastern Steppe has been occupied since the early Upper Paleolithic (ca. 34,000 cal BP) (Devièse et al, 2019), and recent paleogenomic studies suggest that the eastern Eurasian forest-steppe zone was genetically structured during the Pre-Bronze and Early Bronze Age periods, with a strong west-east admixture cline of ancestry stretching from Botai in central Kazakhstan to Lake Baikal in southern Siberia to Devil’s Gate Cave in the Russian Far East (de Barros Damgaard et al, 2018; Jeong et al, 2018; Sikora et al, 2019; Siska et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we have shown that two sets of genes associated with self-domestication and NC development and function, respectively, have been selected during the last 6,000 years in Europe, a period when important changes in human behavior and culture occurred, including the spread of agricultural practices and sedentism, urbanization, increasing in population density, development of trading routs, globalization etc. These changes reshaped not only the gene pool of Europe, but also modified its linguistic landscape, because Neolithic languages were almost totally replaced by Indo-European languages (Bouckaert et al, 2012;de Barros et al, 2018;Mathieson, 2018, among many others).…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that they incorporated this practice via migration from the Yamnaya, another group of horse herders that likely introduced this practice into Europe via a large-scale migration in the Bronze Age 5,15 . A recent study, however, showed that the Botai and the Yamnaya do not share strong genetic affinities, and that the Botai are closely related to Siberian Paleolithic hunter-gatherer groups 37 . Furthermore, another study on ancient horse DNA indicates that the Botai horses are not particularly closely related to modern horse breeds 38 .…”
Section: Techno-cultural Development and Diffusionmentioning
confidence: 92%